PETROBRÁS: seu papel na política do petróleo e o processo de internacionalização econômica - Araujo, Flavio Santos Tojal de (1996)
Starting from a historical analysis of the aspects that lead the State to get involved in the petroleum matter and, consequently, start a public political instrument such as Petrobras, this theses studies the development of the state company since its foundation, paying special attention to the changes that are being conducted to adjust its role im implementing petroleum politics to the transformations caused by internationalization process of the national economic sustems.